THE COMPARATIVE ANALYSIS OF ENGLISH-UZBEK IDIOMS WITH THE COMPONENT OF «EAR» (Ta'limning zamonaviy transformatsiyasi, 2024)
Annotation: The majority of people today place a high value on learning a foreign language. The majority of people in most nations are acquiring English as a second language. But learning a language involves more than just memorizing words; it also entails becoming familiar with the target language's phrases, idioms, proverbs, and phraseological components.